Roman Catholic worship : Trent to today - White, James F. (New York : Paulist Press, 1995)
The four and one half centuries since the beginning of the council of Trent have witnessed enormous changes in Roman Catholic worship. At the beginning of the era congregations were preoccupied with devotions during the eucharistic liturgy, while today congregations participate actively in the liturgy while nearly ignoring devotions. This book surveys a tradition in translation, during which worship continued to evolve even when liturgical books remained largely unchanged.
A distinctive feature of the present volume is the emphasis it gives to the total worship life of congregations rather than focusing on official documents.
Developments in worship are traced through the epochs since Trent - the baroque age, the enlightenment, the romantic era, the second liturgical movement and the reforms in the wake of Vatican Council II. Cultural changes in each period are viewed through the lenses of church architecture, music, preaching and public prayer. This volume provides a history not only of the mass but all the worship forms in Roman Catholic experience, sacramental rites and popular devotions.
1. The Legacy of the Council of Trent -- 2. The Baroque Age -- 3. The Enlightenment -- 4. The Romantic Era -- 5. The Second Liturgical Movement -- 6. The Age of Reform -- 7. The Future of Roman Catholic Worship.
Includes bibliographical references (p. 150-162) and index.
Keywords: Catholic Church -- Liturgy -- History